Looking on the Bright Side: Aging and the Impact of Emotional Future Simulation on Subsequent Memory - Devitt, Aleea L (J Gerontol B Psychol Sci Soc Sci, 2019)
OBJECTIVES: When younger adults simulated positive future events, subsequent memory is positively biased. In the current studies, we explore age-related changes in the impact of emotional future simulation on subsequent memory. METHODS: In Experiment 1, younger and older adults simulated emotional future events before learning the hypothetical outcome of each event via narratives. Memory was assessed for emotional details contained in those narratives. In Experiment 2, a shorter temporal delay between simulation and narrative encoding was used to reduce decay of simulation memory over time. RESULTS: Future simulation did not bias subsequent memory for older adults in Experiment 1. However, older adults performed similar to younger adults in Experiment 2, with more liberal responses to positive information after positive simulation. DISCUSSION: The impact of an optimistic outlook on subsequent memory is reduced with age, which may be at least partly attributable to declining memory for future simulations over time. This work broadens our understanding of the functional consequences of age-related declines in episodic future simulation and adds to previous work showing reduced benefits of simulation with age on tasks tapping adaptive functions.